CYTOTOXICITY OF CIPADESSA BACCIFERA (ROTH.) MIQ . ON HELA, JURKAT, MCF-7, AND KB CELL LINES - K.R. KAVITHA,; A.K. BOPAIAH,; H. RAMAKRISHNAIAH,; N. NAVEEN KUMAR, (International Journal of Pharma and Bio Sciences, 2015)
Cipadessa baccifera (Roth.) Miq., belongs to Meliaceae family, is an ethnobotanically important plant. The aim of this study was to evaluate the cytotoxic activity of methanolic extracts of root, stem bark, leaf and fruit of C. baccifera against HeLa, MCF-7, Jurkat, and KB cell lines. Methanolic extracts of different plant parts were obtained and assessed for their cytotoxic activity by the MTT assay method. Leaf and root extracts showed potent cytotoxicity against MCF-7 and KB cell lines with significant IC50 values. Fruit extract showed moderate cytotoxicity against HeLa and Jurkat cells. Cytotoxicity of bark extract was moderate on KB cells. Differential cytotoxicity was observed against the cell lines. Significant cytotoxic activity was reported in leaf and root extracts on MCF-7 and KB cell lines. Detailed cytotoxic evaluation of leaf and root extracts along with isolation and characterization of compounds is promising in the formulation of anticancer drugs against human breast cancer and human nasopharyngeal epidermoid cancer.